2014
DOI: 10.1002/2014ja019779
|View full text |Cite
|
Sign up to set email alerts
|

Electron number density, temperature, and energy density at GEO and links to the solar wind: A simple predictive capability

Abstract: Many authors have studied the outer radiation belts response to different solar wind drivers, with the majority investigating electron flux variations. Using partial moments (electron number density, temperature, and energy density) from GOES‐13 during 2011 allows for changes in the number of electrons and the temperature of the electrons to be distinguished, which is not possible with the outputs of individual instrument channels. This study aims to produce a coarse predictive capability of the partial moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
(76 reference statements)
5
17
0
Order By: Relevance
“…Lyatsky and Khazanov [] further hinted that solar wind density might be a more important controlling factor of relativistic electron fluxes at geostationary orbit than solar wind velocity over shorter timescales (less than 10 h) following the start of solar wind changes (similar results were obtained by Potapov et al [], in their Figure 3), with a larger density corresponding to lower electron fluxes. Balikhin et al [] and Boynton et al [] found that the solar wind density controls a majority of the 1.8–3.5 MeV electron flux variance, and a similar anticorrelation was also found by Hartley et al []. Thus, increases of southward IMF B s or solar wind dynamic pressure p , as well as increases of the solar wind density n , may all concur to various degrees, together or separately, to produce strong electron flux dropouts in various energy ranges.…”
Section: Solar Wind and Geomagnetic Activity Influence On Dropoutsmentioning
confidence: 66%
“…Lyatsky and Khazanov [] further hinted that solar wind density might be a more important controlling factor of relativistic electron fluxes at geostationary orbit than solar wind velocity over shorter timescales (less than 10 h) following the start of solar wind changes (similar results were obtained by Potapov et al [], in their Figure 3), with a larger density corresponding to lower electron fluxes. Balikhin et al [] and Boynton et al [] found that the solar wind density controls a majority of the 1.8–3.5 MeV electron flux variance, and a similar anticorrelation was also found by Hartley et al []. Thus, increases of southward IMF B s or solar wind dynamic pressure p , as well as increases of the solar wind density n , may all concur to various degrees, together or separately, to produce strong electron flux dropouts in various energy ranges.…”
Section: Solar Wind and Geomagnetic Activity Influence On Dropoutsmentioning
confidence: 66%
“…Their results showed that electron fluxes have a positive correlation with the solar wind speed, while middle-to high-energy fluxes show anticorrelation with the solar wind density. Hartley et al (2014) used MAGED 30-600 keV electron data of year 2011 from the GOES-13 geostationary satellite to determine the effect of solar wind speed and density on the electron density, temperature, and energy density at the geostationary orbit. They found that simultaneously elevated electron number density and temperature are usually preceded by fast solar wind speed about 24 h previous.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the fact that satellites located in this orbit have an orbital period of 24 h, allowing them to remain at the same geographic longitude above the Earth during their operational lifetime. Predictions of the plasma environment encountered by satellites at GEO [Purvis et al, 1984;O'Brien and Lemon, 2007;Thomsen et al, 2007;Sicard-Piet et al, 2008;O'Brien, 2009;Ginet et al, 2014;Hartley et al, 2014;Ganushkina et al, 2013Ganushkina et al, , 2014Ganushkina et al, , 2015Denton et al, 2015] provide spacecraft designers and operators with estimates of the plasma conditions (e.g., the ion flux and the electron flux) that satellite hardware will be subjected to on orbit. If such predictions are based on upstream solar wind conditions (e.g., measured by the ACE satellite or the DSCOVR satellite situated in Lissajous orbits at the L1 Lagrangian point between the Earth and the Sun), then this allows a lead time of around 1 h from the flux predictions being made to when such fluxes may be encountered.…”
Section: Introductionmentioning
confidence: 99%